Relasi Media dan Kekuasaan Politik di Indonesia dari Perspektif Ekonomi Politik Komunikasi Vincent Mosco - Agus Rahmat; Nani Nurani Muksin (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2025)
The relationship between the media and power in Indonesia has undergone a shift in the dominant actors exercising strict control. The Orde Baru and Orde Lama were dominated by the state. After the state weakened following the 1998 Reformation, researchers found that the desired freedom and independence of the press had been fully realized. The relationship between the media and power continues to exist, although it is no longer the state, but rather market or economic interests and media owners. This study examines this relationship pattern from Vincent Mosco's perspective on the political economy of communication. Keyword: mass media, political power, political economy of communication, vincent mosco, Indonesian press.